2020
DOI: 10.2147/ott.s278736
|View full text |Cite
|
Sign up to set email alerts
|

<p>CD26 as a Promising Biomarker for Predicting Prognosis in Patients with Pancreatic Tumors</p>

Abstract: Purpose Pancreatic cancer is associated with a high mortality rate owing to insufficient approaches for early diagnosis and the invasive biological behavior of the cancer. CD26 is a membrane-anchored protein involved in multiple physiological and pathological processes. Here, we investigated correlations between CD26 expression and clinicopathological features in patients with pancreatic tumors. Methods We collected 170 tumor tissue specimens and 138 paired paratumoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…20,21 Recently, over-expression of CD26 was founded in several cancers, including malignant mesothelioma, 22 thyroid cancer, 23 urothelial cancer, 24 and pancreatic cancer. 25 In contrast, under-expression of CD26 has also been reported in colorectal cancer (CRC). Cordero et al reported decreased serum CD26 levels in patients with CRC compared to healthy controls in early CRC.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Recently, over-expression of CD26 was founded in several cancers, including malignant mesothelioma, 22 thyroid cancer, 23 urothelial cancer, 24 and pancreatic cancer. 25 In contrast, under-expression of CD26 has also been reported in colorectal cancer (CRC). Cordero et al reported decreased serum CD26 levels in patients with CRC compared to healthy controls in early CRC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increased CD26 expression level has been associated with poor prognosis in pancreatic cancer patients [ 46 ] and other cancers [ 40 , 50 ]. DPP-4 expression in the primary tumor may regulate cancer behavior; however, the expression of DPP-4 in the primary tumor appears to be the heterogeneity patterns, depending on tumor type, stage, microenvironment, and host condition.…”
Section: Dpp-4 Expression In Primary Tumorsmentioning
confidence: 99%
“…DPP4 is an oncogene or tumor suppressor gene in different tumors in humans. Overexpression of DPP4 is associated with poor survival in patients with squamous cell lung cancer [ 9 ], hepatocellular carcinoma [ 10 ], renal clear cell carcinoma [ 11 ], pancreatic carcinoma [ 12 ], and colorectal cancer [ 13 ]. However, DPP4 is a tumor suppressor in nonsmall cell lung cancer [ 14 ], ovarian cancer [ 15 ], endometrial cancer [ 16 ], and prostatic cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%